A Posterior Lingual Sulcoplasty in Implant Therapy: A Case History Report - Perri de Carvalho, Paulo Sergio; Janjacomo, Luiz Antonio; Ponzoni, Daniela (Quintessence Publishing Co Inc, 2016)
This case history report describes the deepening of a patient's posterior mandibular lingual sulcus in combination with an acrylic resin guiding device fixed to an osseointegrated dental implant to maintain the patency of the new sulcular depth.